ANALISIS GERAK TARI INDANG TAGAK DI JORONG DURIAN TARUANG KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Maulida Khaira Fauzia; Desfiarni (Universitas Negeri Padang, 2026)
This study aims to describe and analyse the Indang Tagak Dance Movements in Jorong Durian Taruang, Sangir District, South Solok Regency. This research is qualitative with a descriptive approach method. The research instrument is the researcher themselves, supported by stationery, a camera and a mobile phone. The data used consist of primary and secondary data. Data were collected through literature review, observation, interviews and documentation. The steps for analysing the data are data collection, data reduction, data presentation and drawing conclusions. The results indicate that the analysis of Indang Tagak Dance Movements in Jorong Durian Taruang, Sangir District, South Solok Regency consists of spatial, temporal and energy aspects in which these three elements blend to form distinctive and meaningful movement characteristics. The spatial aspect of this dance is characterised by straight lines, small movement volumes, forward-facing direction, low levels, and focus directed forward and downward. All these elements reflect values of order, simplicity, devotion, and respect, which align with Islamic teachings and Minangkabau culture. Meanwhile, the temporal aspect is seen in the dynamics of changing tempo and rhythm throughout the performance. It begins with a slow tempo that creates a solemn atmosphere, then rises to a fast and spirited pace in the middle section, and slows again at the end as a form of respect for the Prophet Muhammad PBUH. This change in tempo not only enriches the aesthetics of the performance but also reinforces the message of togetherness. Meanwhile, the internal energy aspect in the dance movements shows variations in intensity and pressure adjusted to the verses and rhythm. The gentle and light movements at the beginning and end of the performance depict calmness and immersion, while the strong and firm movements in the middle reflect the collective spirit and unity of the dancers.